Zur Problematik von Begriffsbestimmungen und das Beispiel der ländlichen Bevölkerung - Wenzel, Hans-Joachim (ERDKUNDE, 1977)
This paper is concerned with the problem of terminological conceptions and definitions, taking the case of rural population as an example. On the theoretical plain terminological formation is discussed, on the one hand, in its dependence on social evaluation and conception, and, on the other hand, in its dependence on the structure of characteristics upon which it is based. For this purpose the setting-up of a so-called terminological frameworkas a frame for characteristics and conceptions is proposed, which embraces the most important criteria and characteristics for typological registration. With the help of this instrumentarium it is not only possible to define types and forms of rural population phenomena and to classify them but also the framework terms themselves, so as to make possible a regional and temporal comparison of agrarian-social types and forms. The criteria of definition employed here are the characteristics of kinds of landed property and land holding and ways and means of land utilisation.